Interelement Decoupling Strategies at UHF MRI - Zivkovic, Irena (Frontiers in Physics, 2021)
Moving to the ultrahigh field magnetic resonance imaging (UHF MRI) brought many benefits such as potentially higher signal-to-noise ratio, contrast-to-noise ratio, and improved spectral resolution. The UHF MRI regime also introduced some challenges which could prevent full exploitation of mentioned advantages. A higher static magnetic field means increase in Larmor frequency, which further implies the shorter wavelength in a tissue. The shorter wavelength causes interferences of the RF signal and inhomogeneous excitation, which can be partially resolved by the introduction of the multichannel coil arrays. The biggest problem in UHF multichannel densely populated arrays is the existence of the interelement coupling, which should be minimized as much as possible. This article presents the nonconventional, recently developed decoupling techniques used in UHF MRI.